Formation of Health Preserving Competence of the Future Pre-School Teachers in the Process of Professional Training (Ascertaining Stage of the Experiment) - Kravchuk, Nelia (Pedagogical Discourse, 2016)
The problem of health-preserving competence of student’s youth was, is and always will be relevant, because a healthy young generation is the highest value and the property of the state. The above displays one of the first places education as one of directions of solving the problem of formation of health protection competence in the future teachers of preschool educational institutions in the process of professional training and organization of quality education implies coherence between all participants of the educational process. The education system needs to take care of the youth as the future of the nation: to teach the culture of health, to form health-preserving competence, to teach the youth to conserve, restore and improve health throughout life. The purpose of this article is to highlight the results of stating stage of experimental research. Regularities of the process of formation of health-preserving competence from the students of higher educational institutions have become the subject of study of many scientists (Bobrytska V., Voronin D., Savidis N., Zdanuk ). in their efforts, and developing innovative approaches to the training of a healthy lifestyle students and scientific approaches to the use of health saving technologies in the context of the higher educational institutions. The article described in detail the results of stating stage of experimental research of the state of development of health competence in future teachers of preschool educational institutions in the process of professional training. Ascertaining the stage of experimental research was conducted over 2014-2015 on the basis of higher educational institutions of I – II levels of accreditation. The study involved 309 students of pedagogical educational institutions, and 50 educators’ preschool educational, a comparative analysis of results of answers of respondents in both groups, which are presented in the article. In the course of the experiment substantiated the level of awareness of the respondents in the field of health care, understanding the major concepts, factors, means of conservation, enhancement and restoration of health, the value of using health-saving technologies in the educational process, and, consequently, the degree of formation of health-preserving competence. Key words: health-preserving competence, educators’ of preschool educational establishment, healthy lifestyle, experimental research.